159k views
3 votes
Icated (Q#1-4).

2. Solve by substitution; x+3y + 4)
3x - 5y = 8
3 (3x+4)
aytla

User Adiana
by
5.2k points

1 Answer

2 votes

Answer:

See explanation

Explanation:

Assuming your system is:


x + 3y = 4


3x - 5y = 8

Then make x the subject in the first equation to get:


x = 4 - 3y

Put this equation into the second equation to get:


3(4 - 3y) - 5y = 8


12 - 9y - 5y = 8


- 9y - 5y = 8 - 12


-14y = - 4


y = ( - 4)/( - 14) = (2)/(7)

This means that:


x = 4 - 3 * (2)/(7)


x = 4 - (6)/(7) = (22)/(7)

User Mazzi
by
5.2k points